Hubungan Dukungan Suami dengan Perilaku Sadari Pada Ibu di Kecamatan Kumelembuai - Sumakul, Virgie Beverly; Natalia, Adriani; Fernandez, Gratsia Victoria (Mapalus Nursing Science Journal, 2025)
Background: The increasing incidence of breast cancer in Indonesia has become the cancer with the highest incidence in women. Self-Breast Examination (BSE) behavior is one of the primary prevention efforts that can be done, therefore to support BSE behavior, the involvement or support of the husband as a family is needed. Aim: To determine whether there is a relationship between husband's support and BSE behavior in mothers in Kumelembuai District. Method: The research design used in this study was a correlative design using a cross-sectional study approach. The sampling technique used in this study was Non Probability Sampling with Purposive Sampling sampling. Results: The results of the Spearman rho statistical test showed a moderate significance value of p value 0.000 <0.05, so Ha was accepted, thus there was a positive correlation between husband's support and mother's SADARI behavior. Conclusion: There is a significant relationship between husband's support and SADARI behavior. Keywords: Breast Cancer, Husband’s Support, Self-Breast Examination Behavior